To the question of improving the legal regulation of the atomic energy waste management - Shastouskaya, Sviatlana A. (Journal of the Belarusian State University. Law, 2020)
It’s stated in the article that the legislation of the Republic of Belarus in the field of nuclear waste management establishes requirements for selecting sites for the installation of radioactive waste management facilities, the requirements for the design, construction, operation and closure of these plants, as well as the assessment of security related facilities. Legal regulation in this area should be developed in such a way that negative impact on the environment is minimized, and the environmental rights of everyone are protected. Some measures to improve the legislation in this area are proposed. It is concluded that it is necessary to increase scientific validity, ensure a systematic and differentiated approaches in establishing environmental and legal requirements in the field of nuclear waste management, and increase the number of direct rules in legislative acts regulating the relevant relations. It is proposed to consolidate in law the concept of «life cycle of a nuclear waste storage facility».